Firefighters’ exposure to per-and polyfluoroalkyl substances (PFAS) as an occupational hazard: A review - Mazumder, Nur-Us-Shafa; Hossain, Md Tanjim; Jahura, Fatema Tuj; Girase, Arjunsing; Hall, Andrew Stephen; Lu, Jingtian; Ormond, R. Bryan (Frontiers in Materials, 2023)
The term “firefighter” and “cancer” have become so intertwined in the past decade that they are now nearly inseparable. Occupational exposure of firefighters to carcinogenic chemicals may increase their risk of developing different types of cancer. PFAS are one of the major classes of carcinogenic chemicals that firefighters are exposed to as occupational hazard. Elevated levels of PFAS have been observed in firefighters’ blood serum in recent studies. Possible sources of occupational exposure to PFAS include turnout gear, aqueous film-forming foam, and air and dust at both the fire scene and fire station. Preliminary discussion on PFAS includes definition, classification, and chemical structure. The review is then followed by identifying the sources of PFAS that firefighters may encounter as an occupational hazard. The structural properties of the PFAS used in identified sources, their degradation, and exposure pathways are reviewed. The elevated level of PFAS in the blood serum and how this might associate with an increased risk of cancer is discussed. Our review shows a significant amount of PFAS on turnout gear and their migration to untreated layers, and how turnout gear itself might be a potential source of PFAS exposure. PFAS from aqueous film-forming foams (AFFF), air, and dust of fire stations have been already established as potential exposure sources. Studies on firefighters’ cancer suggest that firefighters have a higher cancer risk compared to the general population. This review suggests that increased exposure to PFAS as an occupational hazard could be a potential cancer risk for firefighters.